2021
DOI: 10.48550/arxiv.2111.07329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalised Ellis-Bronnikov wormholes embedded in warped braneworld background and energy conditions

Vivek Sharma,
Suman Ghosh

Abstract: Ellis-Bronnikov (EB) wormholes require violation of null energy conditions at the 'throat'. This problem was cured by a simple modification of the 'shape function', which introduces a new parameter m ≥ 2 (m = 2 corresponds to the EB model). This leads to a generalised (GEB) version. In this work, we consider a model where the GEB wormhole geometry is embedded in a five dimensional warped background. We studied the status of all the energy conditions in detail for both EB and GEB embedding. We present our resul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In 5D scenario, we also have the effective potential V y (λ) corresponding to the motion along the extra dimension as well. Note that here we only consider m = 2 case as advantages of m > 2 is provided by the warped extra dimension as demonstrated in [91].…”
Section: D-wgeb Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In 5D scenario, we also have the effective potential V y (λ) corresponding to the motion along the extra dimension as well. Note that here we only consider m = 2 case as advantages of m > 2 is provided by the warped extra dimension as demonstrated in [91].…”
Section: D-wgeb Modelmentioning
confidence: 99%
“…In [91], we demonstrated that a warped GEB (5D-WGEB) model, where a generalized version of Ellis-Bronnikov spacetime is embedded in a 5D warped background, satisfies the energy conditions, even for m = 2. Therefore, in this work also we shall focus mostly on the original E-B geometry embedded in 5D warped background (5D-WEB).…”
Section: Introductionmentioning
confidence: 99%
“…In [89], we demonstrated that a warped GEB (5D-WGEB) model, where a generalized version of Ellis-Bronnikov spacetime is embedded in a 5D warped background, satisfies the energy conditions, even for m = 2. Therefore, in this work also we shall focus mostly on the original E-B geometry embedded in 5D warped background (5D-WEB).…”
Section: Introductionmentioning
confidence: 99%